Answer:
1) x=−4, y=−20
2) x=−1, y=3
3) x = 7 , y=4
4) x = -6.5 , y = -10.5
Step-by-step explanation:
1) y=5x;−3x+2y=−28
solving system by substitution:
substitute y =5x into 2nd equation:
-3x +2*5x =-28 → -3x+10x = -28 → 7x = -28 → x = -4
plug in x in any equation and solve for y = 5* -4 = -20
2) solving system by elimination:
Multiply the first equation by 7, and the second equation by 5.
7(4x−5y=−19)
5(3x+7y=18)
----------------------
28x−35y=−133
15x+ 35y= 90
Add them up to eliminate y:
43x=−43 divide both sides by 43
x=−1
plug x back into 1st equation to solve for y
4x−5y=−19
(4)(−1)−5y=−19
−5y−4=−19 add 4 to both sides
−5y=−15 divide by -5
y=3
3) y =4 , 5x -6y = 11
plug in 4 for y in 2nd equation and solve for x:
5x -6* 4 =11 simplify
5x - 24 = 11 add 24 on each side
5x = 11 +24 simplify
5x = 35 divide by 5 on each side
x =7
4) y = x -4, 2x - y = -2.5
use substitution method:
2x -(x-4) = -2.5 distribute ( )
2x-x+4 = -2.5 simplify
x + 4 = -2.5 subtract 4 on each side
x = -2.5 -4
x = -6.5
plug in -6.5 for x in 1st equation and solve for y:
y = -6.5 -4
y = -10.5